Analisis Tingkat Motivasi Latihan Pada Atlet Karate Lembaga Karate-do Indonesia (Lemkari) Kategori Kumite di Jawa Tengah - Alviani Dyah Rahmawati; Inosen Lingsir Maghribi; Dasih Ayu Wulansari; Saddan Pramana Putra (Athena: Physical Education and Sports Journal, 2026)
This study aimed to analyze training motivation among Lemkari karate athletes in the kumite category in Central Java. The research employed a descriptive quantitative approach using a survey method. The participants consisted of 30 beginner to cadet kumite athletes aged 13–17 years selected through purposive sampling. The research instrument was adapted from The Psychological Skills Inventory for Sport, translated into Indonesian, adjusted to the context of martial arts, and validated by language experts, martial arts experts, and sports psychology experts. Data were collected using a Likert-scale questionnaire. Data analysis was conducted using descriptive percentage statistics with the assistance of IBM SPSS Statistics version 27.0.1.0. The results showed that the athletes’ training motivation was categorized as moderate, with a mean score of 37.40. The categorization results indicated that 40% of athletes were in the moderate category, 30% in the low category, 26.67% in the high category, and 3.33% in the very low category. These findings indicate that athletes’ training motivation still needs improvement through coaching approaches that consider psychological aspects in addition to physical and technical aspects.